Beyond the victim : the politics and ethics of empowering Cairo's street children - Fahmī, Kamāl (American University in Cairo Press, 2007)
Kamal Fahmi draws on eight years of fieldwork with street children in Cairo to portray them in a different - and empowering - light. Fahmi argues that, far from being mere victims or deviants, these children, in running away from alienating home lives and finding relative freedom in the street, are capable of actively defining their situations in their own terms.